2023
DOI: 10.3389/fpubh.2023.1163616
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination coverage and its cognitive determinants among older adults in Shanghai, China, during the COVID-19 epidemic

Abstract: ObjectivesThis study aimed to examine the coverage of coronavirus disease 2019 (COVID-19) vaccination and its cognitive determinants among older adults.MethodsA cross-sectional study was conducted using a questionnaire to conduct a survey among 725 Chinese older adults aged 60 years and above in June 2022, 2 months after the mass COVID-19 outbreak in Shanghai, China. The questionnaire covered demographic characteristics, COVID-19 vaccination status, internal risk perception, knowledge, and attitude toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Related publications have proven that the COVID-19 vaccination acceptance rate among the individuals aged 75 years and older is significantly lower as compared to older adults aged 65–74 years [ 64 ]. Similar conclusions were arrived at by Wei et al [ 56 ], as they were indicative of an explicit declining trend for the vaccination coverage rate among older adults: namely, the older the adults, the lower the vaccination coverage rate. We have not confirmed that particular observation by means of our study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Related publications have proven that the COVID-19 vaccination acceptance rate among the individuals aged 75 years and older is significantly lower as compared to older adults aged 65–74 years [ 64 ]. Similar conclusions were arrived at by Wei et al [ 56 ], as they were indicative of an explicit declining trend for the vaccination coverage rate among older adults: namely, the older the adults, the lower the vaccination coverage rate. We have not confirmed that particular observation by means of our study.…”
Section: Discussionsupporting
confidence: 86%
“…The related literature also refers to countries in which the level of acceptance of vaccination in the case of the population of older adults is significantly lower. The study conducted by Wei et al [ 56 ] indicated that 78.3% of older adults have been vaccinated against COVID-19, and for slightly more than a half of them, a booster dose had been administered. A study conducted in Hong Kong (68.6%) indicated that 46.3% of respondents ≥55 of age were willing to be vaccinated against COVID-19 [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations